2018
DOI: 10.3390/met8080576
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Dependence of Material Strength in AA5xxx Series Aluminum Alloys and Evaluation of Their Constitutive Equation

Abstract: The effect of strain rate on the mechanical properties of AA5xxx series aluminum alloys containing solute Mg atoms (AA5005, AA5021, AA5082 and AA5182) and pure aluminum (A1070) was investigated within a wide strain rate range of 1.0 × 10−4 to 1.0 × 103 s−1 at room temperature. The A1070 exhibited a positive strain rate dependence of material strength at the investigated strain rates. However, the AA5xxx series aluminum alloys primarily exhibited the negative strain rate dependence of material strength and serr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…At quasi-static rates of strain, obvious serrations in the curves are visible. These are presumably due to the Portevin-Le-Chatelier (PLC) effect, which describes the locking of a moving dislocation due to solute Mg atoms [13]. At higher strain rates, this effect diminishes as the diffusion speed of solute Mg becomes slow compared to the dislocation speed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At quasi-static rates of strain, obvious serrations in the curves are visible. These are presumably due to the Portevin-Le-Chatelier (PLC) effect, which describes the locking of a moving dislocation due to solute Mg atoms [13]. At higher strain rates, this effect diminishes as the diffusion speed of solute Mg becomes slow compared to the dislocation speed.…”
Section: Resultsmentioning
confidence: 99%
“…Our work provides the necessary data and a model to design and simulate such structures, including the effects of strain rate. On the other hand, from a more scientific point of view, it is interesting to see how different strain rate effects of Sc and Mg combine in one aluminium alloy: for moderate strain rates <≈ 10 3 , the addition of Mg mainly leads to negative strain-rate sensitivity [13], while the addition of Sc incurs a pronounced positive strain rate sensitivity [15] for the UTS. For Scalmalloy, with alloying values of 4.4% Mg and 0.73% Sc by weight [10], these effects appear to mutually cancel out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e substrate materials have different responses to the strain rate effect. Previous studies have reported that a negative strain rate dependence of the material strength has been observed for Al-Mg alloys at a quasistatic strain rate, but there is a positive strain rate dependence for a high strain rate [19]. e yielding strain rate of DX51D+Z could increase by approximately 50% from static to intermediate strain rates [20].…”
Section: Methodsmentioning
confidence: 89%
“…Many researchers have carried out the experimental tests at various strain rate conditions and found that the material exhibits an increased yield strength and flow stress with increased strain rate [6][7][8][9][10][11][12], the existing material models developed by the researchers cannot predict, very accurately, the microstructure changes that are taking place during the manufacturing processes [13,14]. During heat deformation, the material undergoes dynamic strain-hardening and dynamic softening (consisting of dynamic recovery (DRV) and dynamic recrystallization (DRX)), resulting in the evolution of the complex microstructure of the deformed material which is directly reflected in the flow stress curves [15].…”
Section: Introductionmentioning
confidence: 99%